Teknologi Digital Matematika Berbasis Quantum Mechanics (QM) - Kartini Hutagaol (Universitas Advent Surya Nusantara, 2025)
Quantum Mechanics-based digital mathematical technology offers great potential in solving complex mathematical problems, including in the solution of linear programming. Linear programming, which is commonly used in various fields such as economics and computer science, requires efficient methods to find optimal solutions. Digital technology that integrates quantum mechanics (Quantum Mechanics - QM) can offer higher speed and efficiency in solving problems compared to conventional methods. This study explores the application of basic quantum mechanics principles in solving linear programming, with a focus on the utilization of quantum algorithms. The findings show that the use of quantum computing in linear programming can provide results that are significantly faster and more efficient compared to conventional methods